Art auctions and art investment in the golden age of British painting - Federico Gabriele Etro; Elena Stepanova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
We analyze the evolution of the price of paintings in London auctions with a unique dataset of over 200,000 sales in the period 1780-1840. We build a price index for the representative painting through hedonic regressions controlling for the characteristics of auctions and paintings and for the artists' fixed effects. The emergence of an efficient secondary art market was an important opportunity for portfolio diversification. Estimating a CAPM model for art investment suggests that British paintings could deliver a higher return compared to imported paintings and an attractive source of diversification relative to the contemporary stock market. This contributed to increase demand for British art and, possibly, to promote the innovations of its Golden Age. While the representative painting of the British school was initially undervalued, new British painters reached foreign prices by the beginning of 1800s.
Keywords: Z11; N0; D4; 330; Art investment; Price of paintings; British Golden Age; Hedonic regressions; CAPM